Softening of Vibrational Modes and Anharmonicity Induced Thermal Conductivity Reduction in a‐Si:H at High Temperatures - Zhuo Chen; Yuejin Yuan; Yanzhou Wang; Penghua Ying; Shouhang Li; Cheng Shao; Wenyang Ding; Gang Zhang; Meng An (Advanced Electronic Materials)
Abstract Hydrogenated amorphous silicon (a‐Si:H) has garnered considerable attention in the semiconductor industry, particularly for its use in solar cells and passivation layers for high‐performance silicon solar cells, owing to its exceptional photoelectric properties and scalable manufacturing processes. A comprehensive understanding of thermal transport mechanism in a‐Si:H is essential for optimizing thermal management and ensuring the reliable operation of these devices. In this study, we developed a neuroevolution machine learning potential based on first‐principles calculations of energy, forces, and virial, which enables accurate modeling of interatomic interaction in both a‐Si:H and a‐Si systems. Using the homogeneous nonequilibrium molecular dynamics (HNEMD) method, this study systematically investigated the thermal conductivity of a‐Si:H and a‐Si across a temperature range of 300–1000 K and hydrogen concentrations ranging from 6 to 12 at%. The simulation results showed that thermal conductivity of a‐Si:H with 12 at% hydrogen is significantly reduced by 41.2% compared to that of a‐Si at 300 K. The spectral thermal conductivity, vibrational density of states and lifetimes of vibrational modes are analyzed, which revealed both the softening of vibrational modes and anharmonicity effects contribute to the reduction of thermal conductivity as temperature and hydrogen concentration increase. Furthermore, the influence of hydrogen concentration and temperature on diffuson and propagon contribution to thermal conductivity of a‐Si:H is quantatively revealed. This study provides valuable insight for developing thermal management strategies in silicon‐based semiconducting devices and advancing the understanding of thermal transport in amorphous systems.